O-Index as a New Assessment Index for Citations - Zahra Foroughi; Safiyeh Tahmasebi Limooni; Mitra Ghiasi (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: There are some strengths and weaknesses in current indicators of scientometrics. This study aimed to present a new index of scientometrics in evaluating scientific output of Iranian medical journals. Materials and methods: This exploratory analytical study was done with a scientometric approach in scientific output of 108 medical science journals indexed in Scopus and 63 scientific output of the universities of medical sciences in Iran, 2018. Data were collected using a checklist that included scientometric factors. The inclusion criteria was to have at least two articles indexed in the Scopus database and at least one citation. The index to be calculated was the ratio of the number of articles with at least one citation to zero according to the Odds index. Results: Findings showed that the mean h-index of journals was 14.06 and the mean O-index was 2.29. In universities, the highest mean values of O-index, h-index, and h5-index were 2.724, 85.8, and 45.7, respectively belonging to type I universities. There were significant relationships in O, h, and h5 indices between the three types of universities (P= 0.000). Conclusion: According to this study, the O-index was correlated with the h-index and could be very useful in evaluating the scientific output of universities and journals alongside other indices.